PENGUKURAN KINERJA BANK KOMERSIAL DENGAN PENDEKATAN EFISIENSI: STUDI TERHADAP PERBANKAN GO PUBLIC DI INDONESIA - Vicky Rahma Putri; Niki Lukviarman (Jurnal Akuntansi dan Auditing Indonesia, 2008)
The study applies non-parametric analytical technique, i.e. Data Envelopment Analysis (DEA) as performance measures of commercial banking in Indonesia. The study observes efficiency of commercial banks listed in the Jakarta Stock Exchange (JSX) by using suggested financial efficiency ratios for the period of 2002-2004. The approach and technique proposed set of empirical references by comparing operating efficiency of commercial banks listed in the JSX. The study departs from previous studies on measures of bank performance through the use of traditional ratios for banking institutions as the output measures and without using the input measures. The proposed model was also compared to the well-known input-output analysis and simple ratio analysis. The study found that, among commercial banks listed in the JSX during 2002-2004 only 11.8% operates in an efficiently manner. As such, the study reveals that the DEA analysis could be used as either alternative or complementary measures to conventional ratio analysis to evaluate organizational performance, particularly in banking organization. Keyword: Commercial Bank, Efficiency, Data Envelopment Analysis, Governance